Tindak Pidana Korupsi dan Alokasi Dana Desa - Salmon, Harly Clifford Jonas; Saimima, Judy Marria (MATAKAO Corruption Law Review, 2023)
Introduction: The village funds that are managed are expected to realize the welfare of the village community. Community welfare can make a country strong and can compete with other countries. To be able to meet the needs of a quality life, it can be seen from how welfare is. Therefore, welfare is the main value that is always pursued so that humans can realize it. One important factor in realizing welfare is the existence of village funds. Efforts to increase awareness of village officials on the management of state finances, in this case the management of village funds for village officials, require counseling on the allocation of village funds and criminal acts of corruption. The low level of understanding and awareness of the law can be caused by the lack of socialization and supervision, this can be seen from the high level of corruption that occurs in Indonesia, especially in rural villages in Indonesia including Maluku, the lack of community access to knowledge of village financial management certainly causes miss management in village financial management. Purposes of the Research: Analyzing Corruption in Village Fund Allocation. Methods of the Research: The research method used is normative juridical, with a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary and tertiary legal materials. Results of the Research: The management of village funds in Indonesia, including in the Maluku region, should aim to improve the welfare of village communities. However, unfortunately, there are several obstacles that hinder the achievement of this goal. Low levels of legal understanding and awareness among village officials and village financial management tools contribute to this problem. Therefore, to overcome this problem, serious efforts are needed to improve understanding and legal awareness related to village fund management. This includes counseling on the allocation of village funds and the impact of corruption crimes. Better education and training should be provided to village officials and staff involved in village financial management. Only in this way can we reduce the level of corruption that harms village communities and the country as a whole.